2016
DOI: 10.1186/s40560-016-0191-y
|View full text |Cite
|
Sign up to set email alerts
|

Perspective on optimizing clinical trials in critical care: how to puzzle out recurrent failures

Abstract: BackgroundCritical care is a complex field of medicine, especially because of its diversity and unpredictability. Mortality rates of the diseases are usually high and patients are critically ill, admitted in emergency, and often have several overlapping diseases. This makes research in critical care also complex because of patients’ conditions and because of the numerous ethical and regulatory requirements and increasing global competition. Many clinical trials in critical care have thus failed and almost no d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…10 Australia New Zealand Intensive Care Research Centre, Melbourne, Australia. 11 Intensive Care Unit, Wesley Hospital, Brisbane, Australia. 12 Intensive Care Unit, Princess Alexandra Hospital, Brisbane, Australia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Australia New Zealand Intensive Care Research Centre, Melbourne, Australia. 11 Intensive Care Unit, Wesley Hospital, Brisbane, Australia. 12 Intensive Care Unit, Princess Alexandra Hospital, Brisbane, Australia.…”
Section: Discussionmentioning
confidence: 99%
“…In oncology trials conducted in North America, academic centres have been reported to enrol more patients than rural and regional centres, and most of the patient recruitment occurs from a small number of sites. In these trials, the pattern of recruitment reflected the Pareto principle or the "80/20" rule [10,11], which states that 80% of the effects arise from 20% of the causes. This principle was first described by an Italian economist, Vilfredo Pareto, who observed that 80% of the land in Italy was owned by 20% of the population and later noted that the same was applicable to other phenomena [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…To confound matters further, bleeding is common in the critically ill, 100 and performing clinical trials in critical care is fraught with challenges 101 . Balancing treatments affecting hemostasis in such unwell patients is often extremely difficult, and harder still to conduct in a rigorous, randomized manner enabling firm conclusions to be drawn.…”
Section: What About Bleeding With Heparin Therapy?mentioning
confidence: 99%
“…Working with resources such as a QUOD and learning from their expertise will be important when supporting mechanistic research of organ donor management. Some of the suggestions to improve recruitment in ICU can be directly translated, whilst other areas require further feasibility work and qualitative research involving donor families, clinical staff and recipients. Looking outside of Europe, we are likely to learn important lessons from a national observational study in Canada that has recently completed recruitment and was designed to describe current organ donation practices, evaluate the effectiveness of interventions and assessed the feasibility of future randomised trials.…”
Section: Donor Optimisationmentioning
confidence: 99%